Wage flexibility and labour market institutions: a meta-analysis - Miquel Clar; Christian Dreger; Raúl Ramos (Institute for the Study of Labor (IZA), 2007)
Evidence during the nineties about the response of real wages to shocks highlights that this response is substantially lower in European countries than in the United States and that there are important differences among European countries. Which are the reasons that explain these different reactions? In this paper, we apply meta-analytical techniques in order to provide a quantitative summary of the available evidence regarding the influence of labour market institutions on real wage flexibility. We find that the design of the study affects the obtained results, and that in more deregulated labour markets with a lower presence of trade unions, this response is particularly larger
urn:nbn:de:101:1-20080425131
Keywords: 330; Reallohn; Schock; Arbeitsmarkt; Meta-Analyse; Theorie